Living well with dementia: enhancing dignity and quality of life, using a novel intervention, Dignity Therapy. (29th December 2015) - Johnston, Bridget; Lawton, Sally; McCaw, Catriona; Law, Emma; Murray, Joyce; Gibb, John; Pringle, Jan; Munro, Gillian; Rodriguez, Cesar
Abstract : Aims and objectives: To assess the feasibility, acceptability and potential effectiveness of Dignity Therapy to improve the quality of life and reduce psychological and spiritual distress in older people with early stage dementia. Background: Dementia is a syndrome with several causes that leads to a progressive decline in multiple areas of functioning. The maintenance of dignity and enhancement of quality of life are key elements of care. Meaningful communication may become more difficult with condition progression. Improvements in communication may have positive effects on the person's quality of life. Dignity Therapy is a short psychotherapeutic intervention that uses a trained therapist to take the person with dementia through a guided interview process, producing a 'generativity' document that creates a lasting, written legacy during a time when they are still able to communicate well. Design and method: This was a feasibility mixed method study. Dignity Therapy was undertaken with patients diagnosed as having early stage dementia. Data were gathe‐red from pre‐ and post‐Dignity Therapy interviews, a focus group, interviews with key stakeholders, and three outcome measures: The Herth Hope Index; The Patient Dignity Inventory; Perceived Quality of Life/Satisfaction with Quality Life Ratings. Findings: This study demonstrated that Dignity Therapy is feasible, acceptable and potentially effective for older people with dementia. Three overarching themes emerged: A life in context, A key to connect and Personal legacy . Conclusions: We recommend that this feasibility study forms the basis for further study, advocating the prospective benefits to patients with dementia, families and nursing practice. Implications for practice: Dignity Therapy, as a psychosocial intervention, has the potential to improve the quality of life and enhance person centred care for people with dementia.